Seeing change in seafood: examining impacts of globalization and climate change on mid-atlantic black american foodways. - Erwin, Valerie; Graham, Ebony; Cumming, Gabriel; Young, Talia (Geographical Review)
Foodways develop as human communities adapt to changing geographic, environmental, and economic circumstances. In this paper, we examine seafood foodways in an urban Black American community in the Mid-Atlantic region of the United States and place those foodways in the context of two northward migrations. The first is the Great Migration, one of the largest human migration events ever—when Black Americans emigrated from the southern United States during the middle of the twentieth century. The second is the more recent and ongoing northward range shifts of marine species along the eastern United States seaboard related to climate change. As fish species continue to move north, availability of culturally familiar seafood species in the region is changing. We use interviews to characterize the culture of seafood consumption among Black residents of Philadelphia, descendants of those that came during the Great Migration. In parallel, we draw upon Atlantic fisheries data, to examine the case of whiting (Merluccius bilinearis), documenting the simultaneous changing abundance and catch of this species over the last two decades. This study illuminates challenges that both globalization and climate change pose for food systems and foodways. Keywords: fish, foodways, Merluccius bilinearis, Philadelphia, silver hake, silver trout, whiting